Atmospheric Cd, Cr, and Zn Deposition in Several Landscape Plants in Mersin, Türkiye - Isinkaralar, Kaan; Koc, Ismail; Erdem, Ramazan; Sevik, Hakan (Springer Science and Business Media LLC, 2022)
The principal problem in dense cities is air pollution and the damage to the environment caused by air pollution. Roadside landscape plants are exposed to air pollutants, especially in small urban centers caused by congested traffic, heating, and industrial enterprises. According to the type of landscape plants, being a good biomonitor varies according to their absorbing capacity of air pollutants. Chromium (Cr), cadmium (Cd), and zinc (Zn) are the leading pollutants originating from emissions. They are selected and negatively affect several landscape plants in high concentrations. This study aimed to determine their concentration changes according to organ and washing status by commonly used 14 landscape species in parks. The heavy metal holding capacity of 14 species used was compared; chromium, cadmium, and zinc concentrations changed significantly depending on the factors evaluated to adsorb them. The ranking of the accumulation levels was determined as Zn > Cr > Cd and was detected at higher levels in unwashed organs than in the others. Chamaecyparis lawsoniana (A. Murr.) Parl. was shown better biomonitoring features on heavy metal accumulation among all species. Its unwashed leaves' deposited Cd, Cr, and Zn were 154 ppb, 6400 ppb, and 39,940 ppb, respectively.
Keywords: Atmospheric Deposition; Biomonitor; Environmental Pollution; Heavy Metals; Plants; Pollution Tolerance Index; Heavy-Metals; Air-Quality; Biomonitors; Bioindicators; 13. Climate action; 11. Sustainability; 6. Clean water